The Development of Reasoned Multiple Choice Test in Interactive Physics Mobile Learning Media (PMLM) of Work and Energy Material to Measure High School Students’ HOTS - Mohamad Heru; Suparno Suparno (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2019)
This research aims to develop a test instrument in form of reasoned multiple choice test in Physics Mobile Learning Media (PMLM) to measure high school students’ HOTS ability. The test instrument developed consists of 20 reasoned multiple choice questions. The validity of the matter conducted by the expert faculty and 5 teachers of physics. Empirical test was conducted on students 250 high school students in serang. The instrument is developed in three steps, which are designing the test, field-testing the test, and assembling the test. The technique of the analysis of the results of the validity of the point about using the criteria Aiken'V. The Empirical test is analyzed by using QUEST and PARSCALE programs. The result of validity test is valid. Based on the empirical test analysis by using the QUEST program, it is found that the 20 items developed are fit to the threshold (INFIT MNSQ) within the range of 0.77 to 1.33. For that reason, the test items are considered valid. Within the items’ difficulty level, there are two question items which exceed the -0.80 to +0.80 threshold, they are the questions number 10 with the value of 1.06 that is in very high difficulty level, and question number 18 with the value of -0.87 that is in very easy difficulty level. Information about items reliability acquired from the PARSCALE program shows that the test instrument developed is more appropriate to be given to respondents with the range of abilities between -2.08 to +2.58. Therefore, the test instrument developed is suitable to measure the students’ HOTS ability.